Significant Contributions of Volcanic Aerosols to Decadal Changes in the Stratospheric Circulation. Issue 20 (30th October 2017) - Diallo, M.; Ploeger, F.; Konopka, P.; Birner, T.; Müller, R.; Riese, M.; Garny, H.; Legras, B.; Ray, E.; Berthet, G.; Jegou, F.
Abstract: The stratospheric circulation is an important element of climate as it determines the concentration of radiatively active species like water vapor and aerosol above the tropopause. Climate models predict that increasing greenhouse gas levels speed up the stratospheric circulation. However, these results have been challenged by observational estimates of the circulation strength, constituting an uncertainty in current climate simulations. Here, we quantify the effect of volcanic aerosol on the stratospheric circulation focusing on the Mount Pinatubo eruption and discussing further the minor extratropical volcanic eruptions after 2008. We show that the observed pattern of decadal circulation change over the past decades is substantially driven by volcanic aerosol injections. Thus, climate model simulations need to realistically take into account the effect of volcanic eruptions, including the minor eruptions after 2008, for a reliable reproduction of observed stratospheric circulation changes. Plain Language Summary: The upper atmospheric circulation is an important element in the climate system as it determines the distributions and lifetimes of key greenhouse gases and impacts the Earth's radiation budget and surface climate. Current climate models rather uniformly predict that increasing greenhouse gas levels speed up the upper atmospheric circulation. However, these results contrast with observations, constituting a major uncertainty in current climate simulations. Our paper shows that the observed pattern of decadal circulation change over the past few decades is substantially driven by volcanic aerosol injections. The recently observed slowdown of the stratospheric circulation in the Northern Hemisphere is by 50% attributable to stratospheric aerosol from minor volcanic eruptions after 2008, which should no longer be neglected in climate simulations. Key Points: We demonstrate that the volcanic aerosol effect is the primary signal dominating the pattern of decadal variability in the BD circulation Main difference between observations and climate models concerns changes in the depth and strength of the aerosol effect on BD circulation We demonstrate that Northern Hemisphere slowdown is partly driven by minor volcanic eruptions after 2008